Potassium-Efflux Channels in Extensor and Flexor Cells of the Motor Organ of Samanea saman Are Not Identical. Effects of Cytosolic Calcium - Moshelion, Menachem (American Society of Plant Physiologists, 2000)
Leaflet movements in the mimosa-family tree Samanea saman stem from coordinated volume changes of cells in the leaf motor organs in the adaxial and abaxial motor cells (“flexors” and “extensors”). Shrinking, initiated by dissimilar light signals in extensors and in flexors, depends in both cell types on K(+) efflux via depolarization-dependent potassium (K(D)) channels. To compare between flexor and extensor K(D) channels and to test for a possible interaction of these channels with the Ca(2+)-mobilizing phosphoinositide cascade evoked in these motor cells by the “shrinking signals,” we probed the channels with varying (5 nm–3 mm) cytosolic free-Ca(2+) concentration ([Ca(2+)](cyt)) in patch-clamped inside-out excised membrane patches. Ca(2+) was not required for K(D) channel activation. [Ca(2+)](cyt) of 600 nm decreased the mean number of open K(D) channels in flexors, as monitored at −30 mV. Detailed analysis revealed that in flexors millimolar [Ca(2+)](cyt) decreased the maximum number of open channels, but simultaneously increased K(D) channel opening probability by negatively shifting the half-maximum-activation voltage by 40 to 50 mV. Thus, the promoting and the inhibitory effects at millimolar [Ca(2+)](cyt) practically cancelled-out. In contrast to flexors, none of the gating parameters of the extensor K(D) channels were affected by [Ca(2+)](cyt). Irrespective of [Ca(2+)](cyt), the steady-state gating of extensor K(D) channels was slightly but significantly more voltage sensitive than that of flexors. The unitary conductances of flexor and extensor K(D) channels were similar and decreased by approximately 20% at millimolar [Ca(2+)](cyt). It is intriguing that the extensor K(D) channels were significantly less K(+) selective than those in flexors.